2009
DOI: 10.1136/bjo.2009.160671
|View full text |Cite
|
Sign up to set email alerts
|

Use of ultrasonic pachymetry for measurement of changes in corneal thickness in mouse corneal transplant rejection

Abstract: In vivo graft pachymetry provides a new and reliable way to objectively diagnose rejection in the mouse model of corneal transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…6,10,11 Compared to larger animal models, rats are genetically identically inbred, allowing control for many experimental variables. 5 In the present study, we demonstrated that moderate to severe AC inflammation during the early stage after PK could predict graft failure earlier than other indicators. In the rat model, eyes with grade 3 or higher AC inflammation at 1 week or with ‡400 lm central graft thickness at 2 weeks (normal rat corneal thickness, 170 lm), were significant predictors of graft failure at 4 weeks.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations
“…6,10,11 Compared to larger animal models, rats are genetically identically inbred, allowing control for many experimental variables. 5 In the present study, we demonstrated that moderate to severe AC inflammation during the early stage after PK could predict graft failure earlier than other indicators. In the rat model, eyes with grade 3 or higher AC inflammation at 1 week or with ‡400 lm central graft thickness at 2 weeks (normal rat corneal thickness, 170 lm), were significant predictors of graft failure at 4 weeks.…”
Section: Discussionmentioning
confidence: 78%
“…Ultrasonic pachymetry has been evaluated as a possible method for determining allograft rejection in a recent clinical trial, 12 and corneal thickness has been reported to serve as a predictor of graft survival. 16 Flynn et al 5 reported that in vivo graft ultrasound pachymetry provided a reliable way to objectively diagnose rejection in a mouse model of corneal transplantation. Compared to ultrasonic pachymetry, ASOCT is sterile and noncontact, providing more in-depth imaging and micrometric measurements for corneal thickness.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Corneal transplantation and diagnosis of graft rejection were performed as previously described 16. Briefly, recipient mice were anaesthetised with an i.p.…”
Section: Methodsmentioning
confidence: 99%